2015
DOI: 10.1002/jbt.21701
|View full text |Cite
|
Sign up to set email alerts
|

Bone Marrow and Adipose-Derived Mesenchymal Stem Cells Alleviate Methotrexate-Induced Pulmonary Fibrosis in Rat: Comparison with Dexamethasone

Abstract: The present study examined the therapeutic effects of bone marrow mesenchymal stem cells (BM-MSCs) and adipose-derived mesenchymal stem cells (AD-MSCs) in methotrexate (MTX)-induced pulmonary fibrosis in rats as compared with dexamethasone (Dex). MTX (14 mg/kg, as a single dose/week for 2 weeks, p.o.) induced lung fibrosis as marked by elevation of relative lung weight, malondialdehyde, nitrite/nitrate, interleukin-4, transforming growth factor-β1, deposited collagen, as well as increased expression of Bax alo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
18
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(21 citation statements)
references
References 42 publications
2
18
1
Order By: Relevance
“…The authors showed that AD-MSCs had more potential in terms of restoration of hyaluronic acid and suppression of excessive collagen deposition (Hiwatashi et al, 2014;Hiwatashi et al, 2016). Both BM-MSCs and AD-MSCs were considered to have similar potential for treating methotrexate-induced pulmonary fibrosis in rat (Fikry et al, 2015). In a rabbit model of tendon repair, AD-MSCs also exhibited greater treatment potential than BM-MSCs (Behfar et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…The authors showed that AD-MSCs had more potential in terms of restoration of hyaluronic acid and suppression of excessive collagen deposition (Hiwatashi et al, 2014;Hiwatashi et al, 2016). Both BM-MSCs and AD-MSCs were considered to have similar potential for treating methotrexate-induced pulmonary fibrosis in rat (Fikry et al, 2015). In a rabbit model of tendon repair, AD-MSCs also exhibited greater treatment potential than BM-MSCs (Behfar et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…29 In brief, the skin tissues were removed of blood, rapidly frozen in liquid nitrogen and stored at −80°C. 29 In brief, the skin tissues were removed of blood, rapidly frozen in liquid nitrogen and stored at −80°C.…”
Section: Hydroxyproline Contentmentioning
confidence: 99%
“…The hydroxyproline content in the irradiated skin tissues was used to quantify the collagen content using the hydroxyproline analysis kit (Nanjing Jiancheng Bioengineering Institute, A030-2) according to the manufacturer's protocol, since collagen contains approximately 13.5% hydroxyproline. 29 In brief, the skin tissues were removed of blood, rapidly frozen in liquid nitrogen and stored at −80°C. The results are reported as micrograms of hydroxyproline per gram of tissue wet weight.…”
Section: Hydroxyproline Contentmentioning
confidence: 99%
“…Methotrexate has a broad spectrum of side effects, including hematological, gastrointestinal, hepatic and renal toxicities as well as lung fibrosis and cardiac damage . Various preclinical studies investigated regenerative effects of MSCs on methotrexate‐induced cardiac and pulmonary fibrosis, kidney and liver injury and have shown beneficial effects regarding organ regeneration and parenchymal functions . However, as most animal work has been done with allogeneic MSCs, further studies are required to investigate if the observed benefits can also be reproduced with pre‐exposed autologous stem cells.…”
Section: Effects Of Chemotherapeutic Anti‐cancer Agents On Mscsmentioning
confidence: 99%